2007
DOI: 10.3892/ijo.30.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of chromosome X gene expression in primary cultures of normal ovarian surface epithelial cells and epithelial ovarian cancer cell lines

Abstract: The interpretation of loss of heterozygosity (LOH) in cancers is complicated as genes that map to LOH regions may be transcriptionally active (Xa) or inactive (Xi) due to X chromosome inactivation (XCI). We have analyzed the chromosome X transcriptome in four epithelial ovarian cancer (EOC) cell lines (TOV21G, TOV81D, TOV112D, and OV90) and 12 primary cultures of normal ovarian surface epithelial (NOSE) cells in relation to chromosome X integrity. Two-way comparative analysis using HuGeneFL Affymetrix GeneChip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 46 publications
1
48
0
1
Order By: Relevance
“…Although inactivation of one X chromosome over the other is generally random, preferential inactivation of one chromosome (skewed Xi) can protect women against the consequences of X-linked gene mutations 104 . On the contrary the absence of Xi can have detrimental effects: for instance loss of Xist has been reported in breast, ovarian and cervical cancer cell lines 105,106 and, only in female mutant mice, it caused deregulation of hematopoietic lineages and emergence of myeloid neoplasms associated with genome wide changes in gene expression 107 .…”
Section: A) X Chromosomementioning
confidence: 99%
“…Although inactivation of one X chromosome over the other is generally random, preferential inactivation of one chromosome (skewed Xi) can protect women against the consequences of X-linked gene mutations 104 . On the contrary the absence of Xi can have detrimental effects: for instance loss of Xist has been reported in breast, ovarian and cervical cancer cell lines 105,106 and, only in female mutant mice, it caused deregulation of hematopoietic lineages and emergence of myeloid neoplasms associated with genome wide changes in gene expression 107 .…”
Section: A) X Chromosomementioning
confidence: 99%
“…These lncRNAs are involved in various biological processes of ovarian cancer, including chemotherapy, proliferation, apoptosis and metastasis (21)(22)(23)(24). Previous studies have suggested the potential role of lncRNAs in ovarian cancer to a certain extent (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), however, further investigation is required to explain their respective functions and mechanisms of action.…”
mentioning
confidence: 99%
“…X-inactive specific transcript, long stress-induced non-coding transcript 5, Pvt1 oncogene, serum resistance-associated gene and host genes 2 (15)(16)(17)(18)(19)(20). These lncRNAs are involved in various biological processes of ovarian cancer, including chemotherapy, proliferation, apoptosis and metastasis (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…To determine whether the origin of the specimen was fetal or maternal, we extracted DNA from peripheral lymphocytes from the patient and performed a polymerase chain reactionbased genotyping assay using 17 polymorphic microsatellite repeat markers as described elsewhere (1).…”
Section: Case Reportmentioning
confidence: 99%
“…genome.ucsc.edu/cgi-bin/hgGateway). b Genetic markers described in Genome Database (www.gdb.org) and Benoit et al(1). c Results were not obtained in the analysis of tissue DNA for the following genetic markers: D3S1263, D13S1701, MHBPNT2, AR.PCR1, and DX8074.…”
mentioning
confidence: 99%